CREATION OF AN EXPRESSION VECTOR FOR MULTIPLEX EDITING OF THE POTATO VACUOLAR INVERTASE GENE USING THE CRISPR/CAS9 SYSTEM - Akhmetollayeva, A.S.; Manabayeva , Sh.A. (Eurasian Journal of Applied Biotechnology, 2024)
Creating genetic engineering constructs for plant genome editing requires considerable time, material resources, and specialized equipment. A thorough understanding of the functions and efficacy of each construct element is critical to the design of specialized vectors for specific tasks. This article provides a detailed overview of the process of creating genetic engineering constructs for editing the invertase gene responsible for cold-induced sweetening (CIS) in potato tubers, starting with the design of the variable part of the guide RNA and ending with the assembly of the final expression vector for potato cell transformation. For this purpose, an analysis of the nucleotide sequences of the invertase gene from domestic potato varieties was performed, along with a comparative analysis the data from the NCBI database. Optimal targets for gene editing using CRISPR/Cas9 technology were identified and the process of cloning two expression vectors for multiple genome editing was described. The expression vectors obtained allow the knockout of the potato acid invertase gene VInv/Pain-1. Considering that the expression level of Cas9 is a key factor for the efficiency of genome editing, a second expression vector containing the Tomato bushy stunt virus suppressor gene p19 was created to enhance the expression of this gene and the editing efficiency.